The Role of Nurses in Caring Patients with Anxiety Before Undergoing Abdominal Hysterectomy - Chanburee , Suphatida (Journal of Nursing, Siam University, 2020)
Women before having hysterectomy often have anxiety because they consider surgery as a situation that threatens their lives and safety as they anticipate the situation that may arise from surgery. They worry about things they don't know, such as postoperative pain, cancer discovery, undergoing anesthesia, postoperative self-care and postoperative complications. In addition, once they have had a hysterectomy removal of uterus, they will stop having menstrual periods and also no longer be able to get pregnant. After the surgery, they can experience feelings of loss of femininity and loss of sexual desire. All the above problems cause them a lot of anxiety. Therefore, nurses have an important role to support patients to manage their anxiety according to the situation and to address relationships between people and the environment appropriately. The goal of nursing is to reduce or alleviate the anxiety of patients by focusing on dealing with problems, most of which are caused by lack of information or receiving inconsistent information from many sources. Nurses therefore should provide comprehensive and accurate information to meet the needs of patients, provide good advice and recommend ways to manage emotions such as creating imaginations, meditation, deep breathing, using music therapy, etc., for holistic care of patients.